(untitled) (Mutah Journal of Humanities and Social Sciences (MJHSS), 2025)
The study aimed to analyze the competitiveness of Jordanian universities using a descriptive approach through Porter’s Diamond model. The study presented a theoretical framework and reviewed previous studies that explored the experiences of several countries with the competitiveness of their universities. The study found that, despite the ability of Jordanian universities to employ diverse learning methods, the level of innovation and creativity remains modest. Additionally, the proportion of graduate students to total students is still low (8%), as is the percentage of foreign students (12%). The study also indicated that spending on research and development remains insufficient. It further highlighted that government support for public universities is still low, and these universities suffer from chronic budget deficits, leading to accumulated debts. These factors, collectively, hinder the enhancement of the competitiveness of Jordanian universities. Based on these findings, the study recommended increasing the allocation of government spending on scientific research, supporting research initiatives within universities and encouraging researchers to focus on applied research and publish in prestigious international journals. Moreover, the study emphasized the need for the government to increase its financial support for universities and the scientific research fund